(untitled) (Technical Journal, 2019)
In today’s modern dynamic world, automobile industry has seen many revolutions and developments over couple of decades to improve the performance and efficiency. One of the major revolutions was to replace metallic components to high performance polymer composites to reduce total weight of automobiles. As a result we can find more than 50% use of polymer composite and other high performance materials in automobiles like passenger car. In addition to this, the present development is towards making low cost models in cars to make it available to middle class families. Many OEM (Original Equipment Manufacturers) are working for different cost cars for same model to sell across the globe based on the economic status of the countries. Also, unlike metals, which are easily recoverable and recyclable, plastic waste increase forces the government to legislate for the limitation of such waste by introducing the concept of recycling. As a result manufacturers are looking for use of virgin polymer (Polypropylene) along with some percentage of recycled one to reduce the total cost of manufacturing. The present recycling world uses used materials; reprocess them so that they can be used for further applications. This recycling business emphasizes on quantity rather on quality, so mechanical properties actually changes when product made out of Polypropylene are being recycled. The thing is to see how the mechanical strength changes when Polypropylene is recycled and what are the variations in mechanical properties when unused Polypropylene (PP) is mixed with some percentage of Recycled Polypropylene (RPP) along with some percentage of Impact Modifier and Filler material.